Advances in ecological research - Macfadyen, A. (Amyan); Ford, E. D. (Edward David) (Advances in ecological research, 1986)
Jarvis and McNaughton provide a cogent example of the impact of physiological studies in ecology. The study of transpiration is of basic importance in botany and their paper shows how the often conflicting conclusions reached by physiological ecologists and micrometeorologists may be reconciled. Courtney's analysis of Pereid butterfly ecology looks at the various evolutionary strategies adopted by the butterflies, their food plants and their predators and parasites. Franklin and his colleagues have distilled years of research on the decomposition of woody debris into a comprehensive treatment of both the nature and importance of this process in a variety of environments. Vogt and her colleagues also deal with an aspect of decomposition, focusing instead on the importance of the death and decay of root material. Finally, Hartenstein presents a lively discussion on the serious consequences of soil organic carbon deficiency. Combining man made organic waste and earthworm based biotechnology might help in managing carbon poor soils.****FROM THE PREFACE: Over recent years physiological plant ecology has been one of the most active areas of ecological research. It offers a prospect of explaining community function in terms of how the physiological properties of individual plants relate to patterns of microclimate generated in the community itself. However, the strategies of investigation and measurement techniques of the physiological ecologist frequently require very detailed work on just small amounts of material. Providing an integrated assessment of community function from such investigations may not be straightforward.